Effect of autohydrolysis pretreatment On rice straw for sugar production - Siti Norshahirah Binti Saleh (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Rice straw is one of the agriculture by-product in Malaysia. In this study, the rice straw was used to undergo pre-treatment to synthesize sugar. The rice straw was physically pretreated using grinder and it was sieved. The lignocellulosic material then was autohydrolysis pretreated to remove hemicellulose and to breakdown the lignin structure, thus, the lignocellulosic biomass will breaks down into its sugars monomers by using liquid hot water and steam treatment. Liquid hot water was treated where the rice straw was directly contact with water in reactor with optimize two parameter in range 150C -210C and 5 min to 15 min.